Odpowiedzi

2009-12-16T18:07:45+01:00
A) 0,4x+0,3y=1,4/*(-10)
0,1x+3y=2,3

-4X-3y= -14
0,1x+3y=2.3

-3,9x=-11,7/*10

-39x=117/:39
X=3

0,1*3+3y=2,3
0,3+3y=2,3
3y=2,3-0,3
3y=2/:3
y=2/3


b) 2x+3y=14/*2
3x-2y=8/*3


4x+6y=28
9x-6y=24

13x=52/:13
x=4

3*4-2y=8
12-2y=8
-2y=8-12
-2y=-4/(-2)
y=2


c) 3x+4y=1⅔/*3
6x+3y=1¼ /*4



9x+12y=2
24x+12=1/*(-1)


9x+12y=2
-24x-12y=-1

-15x=1/:15
x=1/15

3*1/15+4y=8/3
1/5+4y=8/3

4y=8/3-1/5
4y=40/15-3/15
4y=37/15/:4
y=37/60




1 1 1
Najlepsza Odpowiedź!
2009-12-16T18:08:55+01:00
A)
0,4x+0,3y=1,4 /*10
0,1x+3y=2,3

4x + 3y = 14
0,1x + 3y = 2,3

3y = 14 - 4x
0,1x + 3(14 - 4x) = 14

3y = 14 - 4x
0,1x + 42 - 12x = 14

3y = 14 - 4x
- 11,9x = - 28

3y = 14 - 4x
x = 0,425

3y = 14 - 1,7
x = 0,425

3y = 12,3
x = 0,425

y = 4,1
x = 0,425

b)
2x+3y=14 / * 2
3x-2y=8 / * 3

4x + 6y = 28
9x - 6y = 24

13 x = 52
x = 4

16 + 6y = 28
x = 4

6y = 12
x = 4

y = 2
x = 4

c)
3x+4y=1⅔ /*3
6x+3y=1¼ /*4

9x + 12y = 5
24x + 12y = 5

12y = 5 - 12x
24x + 5 - 12x = 5

12y = 5 - 12x
12x = 0

12y = 5 - 0
x = 0

y = 0,4
x = 0